2022
DOI: 10.31989/ffhd.v12i2.845
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Alpha-amylase inhibition, antioxidant, nutritional and sensory properties of functional spice-blend fortified cookies

Abstract: Introduction: Fortification of foods is often performed to formulate and develop functional foods that improve the nutritional and health status of consumers.     Methods: In this study, a spice-blend (cayenne pepper, garlic and ginger) was incorporated into wheat flour at 5, 10, 15 and 20% for the production of nutritional and healthy cookies. Physicochemical, nutritional, sensory, total phenolics, antioxidant activity and alpha-amylase inhibitory assays of the cookies were performed and compared with control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…According to Noviasari et al [41], polyphenol and flavonoid content found in many foods have great capacity of inhibiting α-amylase and α-glucosidase. Moreover, the phenolic content of rice could be responsible for inhibition of the two enzymes, also legumes (peanuts in this case) and spices are known to be rich in protein, phytochemicals, dietary fibre, vitamins, and other micronutrients beneficial for human health [42][43]. These results agree with Ramakrishna et al [44] who also reported low to moderate alpha-glucosidase inhibition for fermented barley flour extracts.…”
Section: Fkrgsupporting
confidence: 80%
See 1 more Smart Citation
“…According to Noviasari et al [41], polyphenol and flavonoid content found in many foods have great capacity of inhibiting α-amylase and α-glucosidase. Moreover, the phenolic content of rice could be responsible for inhibition of the two enzymes, also legumes (peanuts in this case) and spices are known to be rich in protein, phytochemicals, dietary fibre, vitamins, and other micronutrients beneficial for human health [42][43]. These results agree with Ramakrishna et al [44] who also reported low to moderate alpha-glucosidase inhibition for fermented barley flour extracts.…”
Section: Fkrgsupporting
confidence: 80%
“…According to Ignat et al [42], non-alcoholic cereal-based beverages are healthy drinks that impact positively on human health and their consumption improves liver function, gut microbiota and reduces the incidence of nosocomial infections. Although, fermented foods and beverages may not replace medical treatment, they could serve as adjuvants or alternative therapies in treating and managing the condition through reducing oxidative stress, glycemic control, recovery or maintenance of body weight [43,47].…”
Section: Fkrgmentioning
confidence: 99%
“…They are classified into phenolic acid, coumarin, flavonoid, and tannin [15]. These polyphenols are abundant in beverages, fruits and spices derived from plants such as cacao, grapes, tea, berries, onion, and herbs [16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In all samples of the variety Orange, regardless of the growing region, lycopene was not detected, which may indicate the genetic characteristics of this variety[63]. Lutein and its isomer zeaxanthin help strengthen the vessels' walls and increase their elasticity, as well as improve vision[64][65][66][67].…”
mentioning
confidence: 99%